Taxon-rich multigene phylogeny of the photosynthetic euglenoids (Euglenophyceae) - Kim, Jong Im; Linton, Eric W.; Shin, Woongghi (Frontiers in Ecology and Evolution, 2015)
To establish taxonomy and understand phylogenetic relationships among strains and species of the photosynthetic euglenoids, we performed phylogenetic analyses based on a four gene sequence dataset (nr SSU and LSU rDNA, and pt SSU and LSU rDNA) from 343 taxa (including three outgroup). The phylogenetic tree based on the combined dataset was split into two major clades: Euglenaceae and Phacaceae. The family Euglenaceae was a well-supported monophyletic group containing eight genera (Colacium, Cryptoglena, Euglena, Euglenaformis, Euglenaria, Monomorphina, Strombomonas, and Trachelomonas), each representing a monophyletic lineage, except for the genus Euglena. The genus Euglena was divided into three subclades (A1, A2, and A3) and was paraphyletic due to Euglena archeoplastidiata being grouped with the genus Euglenaria and E. cf. velata with the genus Colacium. The family Phacaceae was supported as a monophyletic group and contained three genera (Discoplastis, Lepocinclis, and Phacus). The genus Phacus contained traditionally defined members as well as the non-traditional P. warszewiczii and P. limnophila, which support the generic concept of Linton et al. (2010).